Workshop Pembuatan Media Pembelajaran Berbasis Canva bagi Guru Taman Kanak-kanak se Kabupaten Barru - amri, nur alim; Martuty, Arie; Hajerah, Hajerah; Ilyas, Sitti Nurhidayah; Syamsuardi, Syamsuardi; Musi, Muhammad Akil (PT Ininnawa Paramacitra Edu, 2025)
The PKM are designed to provide an understanding of the importance of digital literacy skills in the current fast-paced development of digital technology. The service activities were conducted in Barru Regency for early childhood educators, based on interviews and observations that indicated a limited understanding and experience among educators in maximizing the use of digital technology in the learning process. This service was conducted using a workshop model that combined methods of delivering material and hands-on practice in designing, modifying, and developing learning materials using the Canva application. The results of the training showed that educators experienced an increase in motivation to utilize digital applications in learning activities, as well as an improvement in their skills in designing learning materials using the Canva application.